STUDIES ON INNTESTINAL HELMINTHIASIS IN THE SOUTH EAST OF IRAN - E.Ghadirian; F.Arfaa; Gh.Missaghian; K.Keshavarz (Tehran University of Medical Sciences, 1973)
Stool examinations of 402 inhabitants of 8 villages in and around an area near Zahedan, and 280 people who had emigrated from the rural area of Zabol, revealed the following: The prevalence of infection with Ascaris, Trichuris and Trichostrongylus was very low (less than 5%) in all areas surveyed, while the mean infection rates found for H.nana, hookworm and E.vermicularis (by stool examination only) were respectively 25.6%, 14% and 8% for villages in Zahedan and respectively 20.8% , 26% and 12% for the rural area of Zabol. The mean number of eggs of parasites found per gram of faeces was 400 for Ascaris and 1163 for hookworm. The only species of hookworm found was Ancylostoma duodenale, the mean worm burden of which was 18 among 20 cases treated. The species of Trichostrongylus expelled from treated cases were T. orientalis, T.colubriformis and T. vitrinus. The mean worm burden of this parasite was 11.Ninety percent of treated cases expelled E.vermicularis.